Towards Metrology 4.0 in Developing Countries’ Manufacturing Industries - Nzumile, Jailos Mrisho; Mahabi, Victoria; Taifa, Ismail W.R. (Tanzania Journal of Engineering and Technology, 2025)
<span style="color: #333333; font-family: Montserrat, Helvetica, Arial, sans-serif; font-size: 16px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">A systematic literature review was conducted to unveil the status of the digital transformation of metrology in developing countries, as they are lagging in utilising fourth industrial revolution (IR4.0) technologies to transform manufacturing industries. A PRISMA technique was employed using various keywords to identify, screen, and select the relevant literature. Forty publications were selected for the review, mainly discussing IR 4.0 technologies in metrological operations. The results indicate that the digital transformation of metrology has yet to be initiated in developing countries. However, the employment of IR4.0 technologies in advancing metrological operations in manufacturing industries is mostly discussed in the literature, especially in China and India. It was also evident that African countries lag behind their Asian counterparts in utilising the IR4.0 technologies to advance metrological operations in manufacturing industries. To enable sustainable digital transformation in metrology, national measurement institutes, testing and calibration laboratories, and manufacturing industries should embrace utilising IR 4.0 technologies in metrological operations. This will facilitate coordination and harmonisation of metrological operations within the three entities, eventually leading to sustainable digital transformation in metrology. The transformation in developing countries will enable precision, high-quality, and accurate metrological operations in manufacturing industries, leading to increased product quality and industry competitiveness in the international market. Also, industries could save time and cost while reducing errors in performing metrological operations. Moreover, the description of the phases that the manufacturing industries could go through towards Metrology 4.0 is also provided.